2021
DOI: 10.1111/echo.15206
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic function grading by American Society of Echocardiography guidelines and prediction of heart failure readmission and all‐cause mortality in a community‐based cohort

Abstract: Background Diastolic function (DF) guidelines have been simplified but lack extensive outcome data. Using a rural university heart failure (HF) database, we assessed whether DF grading could predict HF, HF readmission, and all‐cause mortality (ACM). Methods In this single‐center retrospective study that included 613 patients in sinus rhythm hospitalized for HF (HF with preserved—254 patients, with mid‐range—216 patients, and reduced ejection fraction—143 patients), we recorded demographics, Doppler‐echo, Frami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this study, we first found that the apelin to NT-proBNP ratio < 0.82 × 10 −2 units had independent from other biomarkers, such as LAVI, E/e', LV hypertrophy and hs-TrT, discriminant potency for HFpEF in T2DM patients' population. Although parameters that strongly describe the severity of LV diastolic dysfunction including LV hypertrophy, LAVI and E/e', have previously demonstrated their clinical and prognostic relevance of determining the HF occurrence, HF admission and all-cause mortality in general population [36][37][38][39], HFpEF continues to be misdiagnosed in T2DM patients [40]. In this context, biomarkers' models appear to be powerful multimodal diagnostic and predictive tools to identify T2DM patients with different degree of adverse cardiac remodeling and stratify them at the risk of HFpEF manifestation [41].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first found that the apelin to NT-proBNP ratio < 0.82 × 10 −2 units had independent from other biomarkers, such as LAVI, E/e', LV hypertrophy and hs-TrT, discriminant potency for HFpEF in T2DM patients' population. Although parameters that strongly describe the severity of LV diastolic dysfunction including LV hypertrophy, LAVI and E/e', have previously demonstrated their clinical and prognostic relevance of determining the HF occurrence, HF admission and all-cause mortality in general population [36][37][38][39], HFpEF continues to be misdiagnosed in T2DM patients [40]. In this context, biomarkers' models appear to be powerful multimodal diagnostic and predictive tools to identify T2DM patients with different degree of adverse cardiac remodeling and stratify them at the risk of HFpEF manifestation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the entire echocardiographic assessment, a single-lead electrocardiogram was recorded. Following the guidelines of the American Society of Echocardiography, a phased-array transducer with a fusion frequency of 2–4 MHz was employed [ 16 ]. Imaging was conducted in M-mode and 2D modes, capturing images in parasternal long-axis, short-axis, apical four-chamber, and two-chamber views and at the aortic root for evaluation.…”
Section: Methodsmentioning
confidence: 99%